Comparison of healthcare utilization among managed Medicaid individuals diagnosed with multiple sclerosis treated with emergent versus established disease modifying therapy. (3rd September 2019) - Parente, Alexis; Sutton, Bryce; Petrilla, Allison; Teigland, Christie
Abstract: Background: Emerging disease-modifying therapies (DMTs) have evolved as an alternative treatment for patients with multiple sclerosis (MS). The efficacy and safety of established DMTs (interferons, glatiramer acetate, natalizumab, fingolimod and mitoxantrone) have been well studied and clinical trials with small sample sizes have suggested that emerging DMTs (iteriflunomide, dimethyl fumarate/BG-12, alemtuzumab and pegylated IFN) may have distinct advantages relative to established DMTs including better outcomes and reduced healthcare resource utilization. However, there is limited real-world information regarding which DMTs (established vs. emerging) provide the best clinical response and outcomes in managed care populations of patients with MS. Aims: To compare MS related healthcare use within one year of initiating emergent and established DMTs among Managed Medicaid individuals diagnosed with MS in the US. Methods: A large national sample of patient-level administrative healthcare claims data was used for this analysis. MS patients aged 18 years and over with a new prescription fill for an established or emergent DMT between 2013 and 2016 were evaluated. Patients were eligible if they were continuously enrolled in a health plan with pharmacy and medical coverage for at least 6 months before and 1 year after initiation of therapy. Four types of healthcare use were examined: MS-related hospitalizations, emergency room (ER) visits and relapse events (inpatient and outpatient). Multivariate negative binomial models with robust standard errors were used to estimate the association between MS related healthcare use and type of DMT. All models adjusted for age, gender, Charlson index and geographic region. Results: During the study period, 6981 Managed Medicaid individuals with a MS diagnosis initiated a DMT. Of those, 79.8% were female, 50.4% were aged 40–64 years and 21.5% were on emergent DMTs. Emergent DMT users had fewer hospitalizations compared to first generation DMT users within one year of initiating therapy (adjusted risk ratio [ARR] = 0.64, 95% confidence interval [CI]: 0.46–0.88) and fewer outpatient relapses (ARR = 0.86%, CI: 0.79–0.95). Differences in inpatient relapses and ER visits were not observed by DMT type. Conclusions: This study suggests emergent DMTs are associated with reduced MS-related hospitalizations and outpatient relapses within one year of initiating therapy. Studies examining a longer treatment time frame and additional outcomes are warranted to confirm these findings.